إتحاد المغرب العربي: قراءة إقتصادية للأهداف من منظور الطرح الوظيفي الجديد - بلقاسمي, رقية (revue mofakir; No 14 (2017): مجلـــة المفكــر, 2018)
This study aims to provide an economic vision for the Arab Maghreb Union with new perspective career, by identifying the conceptual framework for the process of economic integration, and analysis of the theoretical foundations of the new functional approach, by analyzing the founding context of the Arab Maghreb Union, also the objectives of the Maghreb Union with new functional perspective. The study concluded that despite the diversity of objectives contained in the establishing treating of the Maghreb Union on the economic level through treaties and agreements exchanged between the Maghreb countries, but at the practical levels of these goals was not the image expected, cause many difficulties and obstacles that have led to the failure and lack of the effectiveness of the organization as a whole.